Development of light weight sustainable pineapple/kevlar hybridized fiber and peanut husk cellulose toughened vinyl ester biocomposite for unmanned aerial vehicle applications - Bourchak, Mostefa; Ajaj, Rafic; Khalid, Mahmoud; Juhany, Khalid A.; V. R., Arun Prakash; Alshahrani, Hassan (Journal of vinyl & additive technology, 2023)
The aim of this study is to develop a light weight hybrid biocomposite using pineapple and Kevlar fiber with peanut husk cellulose in vinyl ester resin for applications in unmanned aerial vehicles. This study focuses on how the silane treatment on fiber and cellulose particle influences the mechanical, fatigue and low velocity impact properties of this hybrid biocomposites. Using hand lay‐up technique, the biocomposite was prepared with cellulose loading ranging from 1 to 5 vol%. The results revealed that the 5 vol% of cellulose added composite had an improved tensile, impact, flexural, hardness and ILSS of 161 MPa, 224 MPa, 6.8 J, 84 shore‐D and 21.4 MPa. Moreover, the biocomposite with the inclusion of 3 vol% cellulose had an improved fatigue life count of 42 697, 29 821, 22 381 and 18 164 at 25%, 50%, 75% and 90% of UTS. Similarly, the 3 vol% cellulose reinforced composite showed an improved low velocity impact toughness of 12.36 J. The obtained results clearly indicated that these mechanically strengthened and highly toughened biocomposites could be used as working material for number of applications, especially in making of UAVs for the aerospace industry, automotive components for the transportation sector and structural material in domestic infrastructure. Graphical representation of preparation of cellulose particles from peanut husk.